2012
DOI: 10.14743/apem2012.3.138
|View full text |Cite
|
Sign up to set email alerts
|

Parametric optimization of wire electrical discharge machining using TOPSIS method

Abstract: Abstract:In this paper, application of techniques for order preference by similarity to ideal solution (TOPSIS) method is applied for solving multiple criteria (objective) optimization problem in wire electrical discharge machining (WEDM) process. Three examples are included to illustrate the approach. In all the cases, it is found that, the results obtained using the TOPSIS method almost match with those derived by the past researchers which prove the applicability of this method while solving various complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 13 publications
0
38
0
1
Order By: Relevance
“…The basic concept of TOPSIS method is that the chosen alternative should have the shortest distance from the ideal solution and the farthest from the negative-ideal solution (Gadakh, 2012;Saaty, 1980). Each attribute in the decision matrix takes either monotonically increasing or decreasing utility.…”
Section: Topsis Methodsmentioning
confidence: 99%
“…The basic concept of TOPSIS method is that the chosen alternative should have the shortest distance from the ideal solution and the farthest from the negative-ideal solution (Gadakh, 2012;Saaty, 1980). Each attribute in the decision matrix takes either monotonically increasing or decreasing utility.…”
Section: Topsis Methodsmentioning
confidence: 99%
“…Nayak and Mahapatra (2013) used analytic hierarchy process (AHP) and TOPSIS method for optimisation of multi responses such as MRR, surface finish and kerf; they concluded that the methodology is capable of optimising any type of problem with any number of responses. Gadakh (2012) used TOPSIS method for solving multi criteria optimisation problem in wire electro discharge machining process. For optimal process parameter selection a good amount of research has been done using TOPSIS with experimental data for the optimisation.…”
Section: Previous Workmentioning
confidence: 99%
“…TOPSIS was used for Optimization of Multi performance characteristics like MRR and kerf width. The suggested methodology can be employed for any type of selection problem involving any number of selection criterions [23].J.R. Mevadaet.…”
Section: Literature Reviewmentioning
confidence: 99%